Cypress canker: An important disease discovered for the first time on a native South African tree. (28th July 2022) - Wingfield, Michael J.; Marincowitz, Seonju; Pham, Nam Q.; Roets, Francois; Paap, Trudy; Wingfield, Brenda D.; Aylward, Janneke
Abstract: Cypress canker is a branch and stem canker disease of Cupressaceae trees, particularly those in the genera Cupressus and Hesperocyparis . These trees have been planted in many parts of the world as ornamentals and the Seiridium species that cause the disease, consequently, also have an almost global distribution. The taxonomy of Seiridium species causing cypress canker has recently been revised and numerous species are now believed to cause the disease. This study describes, for the first time, cypress canker on the native South African Cupressaceae tree, Widdringtonia nodiflora . The aim was to identify the causal agent and confirm its pathogenicity. Phylogenetic analyses of sequence data for four regions identified the fungus as Seiridium neocupressi, a species previously known only from Australia, New Zealand and Italy. Field inoculations of W . nodiflora branches resulted in distinct cankers within 6 weeks and the fungus could be reisolated from the treated trees. Cypress canker has been known in South Africa for many decades, where it causes a serious disease on nonnative species of Cupressus, but it has never been found on native Cupressaceae. The newly discovered disease caused by a probable alien pathogen is of particular concern because only three species of Widdringtonia occur in South Africa and are important components of the native flora. The two other species, W . wallichii and W . schwartzii, occur in small endemic and threatened populations. The origin of S . neocupressi in South Africa and the relative susceptibility of the three Widdringtonia species, consequently, requires urgent attention. Abstract : Cypress canker caused by Seiridium neocupressi discovered for the first time on Widdringtonia, the only native genus of Cupressaceae in South Africa.